Disproportionately strong climate forcing from extratropical explosive volcanic eruptions - Toohey, Matthew; Krüger, Kirstin; Schmidt, Hauke; Timmreck, Claudia; Sigl, Michael; Stoffel, Markus; Wilson, Rob (Nature Geoscience, 2019)
Funding: This work was supported by the Federal Ministry for Education and Research in Germany (BMBF) through the research program “MiKlip” (grant nos FKZ:01LP130B, 01LP1130A and 01LP1517B). M.T. additionally acknowledges support by the Deutsche Forschungsgemeinschaft (DFG) in the framework of the priority programme “Antarctic Research with comparative investigations in Arctic ice areas” through grant no. TO 967/1-1. K.K. and M.Sigl acknowledge support through the NFR project “VIKINGS” (project no. 275191). C.T. additionally acknowledges support from the European Union project StratoClim (FP7-ENV.2013.6.1-2). Computations were performed at the German Climate Computer Center (DKRZ). Extratropical volcanic eruptions are commonly thought to be less effective at driving large-scale surface cooling than tropical eruptions. However, recent minor extratropical eruptions have produced a measurable climate impact, and proxy records suggest that the most extreme Northern Hemisphere cold period of the Common Era was initiated by an extratropical eruption in 536 ce. Using ice-core-derived volcanic stratospheric sulfur injections and Northern Hemisphere summer temperature reconstructions from tree rings, we show here that in proportion to their estimated stratospheric sulfur injection, extratropical explosive eruptions since 750 ce have produced stronger hemispheric cooling than tropical eruptions. Stratospheric aerosol simulations demonstrate that for eruptions with a sulfur injection magnitude and height equal to that of the 1991 Mount Pinatubo eruption, extratropical eruptions produce time-integrated radiative forcing anomalies over the Northern Hemisphere extratropics up to 80% greater than tropical eruptions, as decreases in aerosol lifetime are overwhelmed by the enhanced radiative impact associated with the relative confinement of aerosol to a single hemisphere. The model results are consistent with the temperature reconstructions, and elucidate how the radiative forcing produced by extratropical eruptions is ...